Athletes must take their place in the vaccine queue, says Coe - Phillips, M. (Reuters, 2020)
Healthy Athletes should take their place in the COVID-19 vaccine queue behind people with more pressing needs despite events such as next year's Olympics looking set to be highly dependent on competitors arriving free from the virus, the head of world athletics Seb Coe said on Friday.